THE BARRIERS TO THE LABOR FORCE PARTICIPATION OF HOUSEWIVES - Bengü HIRLAK (Fırat University, 2019)
It seems important that women's labor force participation for the development of countries. The aim of this study is to determine the reasons behind the decisions of housewives about not working in Kırıkkale Province. For this purpose, a study was done on 260 women who housewife in Kırıkkale. In this study, questionnaire was used as data collection methods. While preparing survey questions were utilized from the related literature and previous works done. In this study, it was applied the questionnaires which consists of two parts. In the first part of the questionnaire was given; to questions related to socio-demographic characteristics of housewives, the second part; to questions related to the barriers to the labor force participation of housewives. The data obtained from the survey was analyzed using the SPSS program. In the research, it has been determined that there is an age difference between the participant housewives and their spouses, most of them are primary and high school graduates and it has been seen that they were not able to have university education due to the familial reasons and being a girl. It has been determined that the housewives have a low previous work experience and they left their previous job since they got married and willingly and almost whole of them are willing to work today. In the result of research, it has been determined that the reasons why they don’t work are firstly their husbands, they don’t want them to work and there is no one to look after their kids and the hardship of working life. In addition to these, it has been determined that there is no significant relationship between the reason why the housewives don’t work and their marriage age, marriage style, training situations, the number of their children.